Research progress on microbial preparation of bacterial cellulose based intelligent color changing materials and their properties - Deger, Sina; Meena, Sanna; Rioz, Sonia (Journal of Green Energy and Environmental Engineering, 2024)
Bio-based aerogel is a lightweight, porous and high specific surface area nanomaterial prepared from natural biomacromolecules, which has shown great potential for application in the food field in recent years.Bio-based aerogels exhibit excellent adsorption, sustained release, and biocompatibility. This review systematically maps how bio-aerogels are made—covering feed-stock choices, sol–gel chemistry and drying routes—then weighs their physical traits and end-use functions. The applications of bio-based aerogels in food preservation mats, food freshness indication labels, nutrient delivery carriers, and fat in artificial meat substitutes were summarized. In addition, the challenges of bio-based aerogels in terms of large-scale production, food safety and consumer acceptance were discussed, and the future development of bio-based aerogels in functional food and industrial production were prospected.